Stepping Through Doorways: An Exploration of Drama in Education, Host Culture and International Schools. - Sipos (Tamas), Chilla (Trinity College (Dublin, Ireland). School of Education, 2020)
Stepping Through Doorways: An Exploration of Drama in Education, Host Culture and International Schools. Chilla Sipos (Tamas) Trinity College Dublin In an increasingly globalised world, intercultural understanding is a key competency required by young people, particularly those who attend international schools. This research explores the use of process drama to capitalise on the rich tapestry of host culture story, such as music, dance and history, to engage international students in the pursuit of intercultural understanding. The study seeks to explore how intercultural understanding might emerge when we integrate drama to engage students with host culture story in the cultural multiplicity of an international school in Budapest. A literature review suggests that intercultural understanding is essential to international education. A research framework and set of indicators was developed from the literature, which informed the research design, analysis and findings in this study. This framework combined several models of intercultural literacy with a framework for dramatic engagement. The research was informed by qualitative methodology, specifically a reflexive practitioner approach. The data collection involved 30 student participants and two teachers in two Humanities classes, who took part in a process drama designed and led by the teacher/researcher and based on host culture story. The findings indicated that the relationship between host culture story, the participants and the reflexive practitioner is integral to progress along the indicators of student engagement and intercultural understanding. The pedagogical qualities particular to drama activated prior experience, enabling participants to inter-act and co-create new realities. It provided a differentiated approach for five participant sub-groups on their individual learning journey, engaging students and enabling them to step into agency through an embodied experience. By scaffolding the elements of drama, playfully exploring perspectives within the dramatic world and reflecting on these events, students attained a level of criticality which could transfer into their own lives, thereby fostering degrees of intercultural understanding. The study reveals that the pedagogical approach of DiE was conducive to engaging those students with host culture story and fostering intercultural understanding. While this study is limited by the small-scale nature of the research, there is potential for further exploration in this area in international schools around the world. Overall, the study shows that infusing the formal curriculum with host culture story can offer a common starting point from which to explore the cultural complexities of the international school setting.
Keywords: Education; Drama in Education